El Método de Casos y el Aprendizaje Significativo del Marketing en la Facultad de Ciencias Empresariales de la Universidad Nacional de Educación Enrique Guzmán y Valle – 2019 - Salas Pittman, Quintter Larry (2021)
The general objective of this thesis is to determine how the case method is related to the meaningful learning of marketing in the Faculty of Business Sciences of the Enrique Guzmán y Valle National University of Education -2019 and as specific objectives, to determine how understanding is related comprehensive, the application of theoretical and technical concepts, the search for correct solutions and the decision-making process with significant learning of marketing. Regarding the methodology, the research approach is quantitative, applied, the research design is non-experimental, transectional or transversal, and the method is hypothetical deductive. Regarding the results, to measure the validity of the content of the instrument, three specialists in the subject were summoned, to establish the reliability, the Cronbach's alpha coefficient has been used, to contrast the hypotheses of the present investigation, it has been used the Spearman Coefficient test, and the results are presented under a descriptive statistical analysis. When analyzing the results of the case method and significant learning variables, it is observed that there is a great relationship since 80.4% of those surveyed consider that the case method is an efficient learning strategy.